2020
DOI: 10.1519/jsc.0000000000003735
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Second Generation Oral Contraceptive Use on Adaptations to Resistance Training in Young Untrained Women

Abstract: Influence of second generation oral contraceptive use on adaptations to resistance training in young untrained women. J Strength Cond Res 36(7): 1801-1809, 2022-The study purpose was to determine effects of using second generation oral contraceptives (OC) on muscle adaptations to resistance training in young untrained women. Twenty users and 18 nonusers of OC completed a 10-week supervised progressive resistance training program. Before and after the intervention, muscle cross-sectional area (mCSA) of the quad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 43 publications
3
25
0
Order By: Relevance
“…A 2-year randomized, controlled trial in female runners indicated that OC assignment was associated with a significant gain in lean mass relative to controls (38), and resistance-trained women using OCs increased lean mass significantly after eight weeks of resistance training whereas non-users did not (39). Furthermore, previous data from our lab demonstrated a greater response to resistance training in untrained 3 rd generation OC users compared to non-users following 10 weeks of resistance training (9), while the effect in 2 nd generation OC users were less pronounced, although trends towards greater gains in lean mass were reported (10). In addition, a recent study by Wallner et al showed a positive effect of providing EE and the progestin Dienogest in physiologic concentrations on human skeletal muscle cell proliferation and myogenic potential in vitro, supporting the notions of an anabolic effect of OCs (49).…”
Section: Introductionmentioning
confidence: 53%
See 4 more Smart Citations
“…A 2-year randomized, controlled trial in female runners indicated that OC assignment was associated with a significant gain in lean mass relative to controls (38), and resistance-trained women using OCs increased lean mass significantly after eight weeks of resistance training whereas non-users did not (39). Furthermore, previous data from our lab demonstrated a greater response to resistance training in untrained 3 rd generation OC users compared to non-users following 10 weeks of resistance training (9), while the effect in 2 nd generation OC users were less pronounced, although trends towards greater gains in lean mass were reported (10). In addition, a recent study by Wallner et al showed a positive effect of providing EE and the progestin Dienogest in physiologic concentrations on human skeletal muscle cell proliferation and myogenic potential in vitro, supporting the notions of an anabolic effect of OCs (49).…”
Section: Introductionmentioning
confidence: 53%
“…This article presents data from a prospective cohort study that was designed primarily to assess the effect of 10-weeks resistance training on gain of muscle mass in 2 nd generation OC users and nonusers (10). Here, we assess the myogenic response to resistance training from muscle biopsies obtained from the study by Dalgaard et al 2020 (10). The study was carried out in accordance with the Declaration of Helsinki, approved by the Central Denmark Region Committees on Health Research Ethics (Journal no.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations